FRI0232 Consistent efficacy and safety outcomes between european and japanese subjects with rheumatoid arthritis following treatment with mavrilimumab in the phase 2 earth study. (23rd January 2014) - Burmester, G.; Takeuchi, T.; Barbarash, O.; Ranganna, G.; Close, D.; Godwood, A.; Saurigny, D.; ,
Abstract : Background: GM-CSF is considered a key mediator in the disease pathogenesis associated with RA. Mavrilimumab (CAM-3001), a human IgG4 mAb that targets GM-CSFRα, may provide clinical benefit to patients with moderate-to-severely active RA. Objectives: To investigate the efficacy and safety of multiple ascending doses (10–100 mg q2w) of mavrilimumab in adult subjects from Europe (EU) and Japan (JA) with active RA. Methods: Subjects (EU n=239; JA n=51) with moderate-to-severely active RA (DAS28-CRP ≥3.2) of ≥3 mos disease duration, receiving stable doses of MTX (7.5–25 mg/wk), and ACPA+ and/or RF+ were randomized 2:1 to subcutaneous mavrilimumab (10, 30, 50, or 100 mg) or placebo (PBO) (safety population); 284 subjects (mavrilimumab 192 [EU n=158; JA n=34]; placebo (PBO) 92 [EU n=75; JA n=17]) were included in the intent-to-treat (ITT) population. Subjects received the study drug every other wk for 12 wks, followed by a 12-wk follow-up (f/u) period. The primary endpoint was the proportion of mavrilimumab subjects achieving a DAS28-CRP decrease ≥1.2 from baseline vs PBO at wk 12. Secondary endpoints included DAS28-CRP<2.6 (remission) and HAQ-DI. Responder analyses were conducted using nonresponder imputation. Safety assessments included laboratory parameters and adverse events (AEs and SAEs). Results: Of the 284 subjects, 264 (93%) (mavrilimumab 182 [95%]; PBO 82 [89%]) completed the study; 2 (1%) mavrilimumab and 2 (2.2%) PBO discontinued due to AEs. Response to mavrilimumab was generally similar in EU and JA subjects. By wk 12, the primary endpoint (DAS28-CRP reduction of ≥1.2) was met by 54.2% of mavrilimumab subjects (EU 55.1% and JA 50.0%) vs 32.6% PBO subjects (p=<.001; EU 34.7; p=.005 and JA 23.5; p=.081). At wk 12, significant improvements with mavrilimumab vs PBO were seen with DAS28 remission (19.8% vs 7.6%; p=.009) and HAQ-DI improvement of ≥0.25 (61.5% vs 46.7%; p=.022). Improvements in the 100 mg group were seen as early as 2 wks (after a single dose) and sustained over the 12-wk f/u period for the DAS primary endpoint (57.4 vs 30.4%; p=.003) and HAQ-DI improvement of ≥0.25 (68.1 vs 44.6%; p=.012). AEs were generally mild/moderate in intensity. The most common AEs are presented in the Table . SAEs were reported in 5 (2.6%) mavrilimumab and 1 (1.0%) PBO subjects; a pneumonia (n=1; mavrilimumab 50 mg; in JA) was considered drug related. Conclusions: In this phase 2 study, outcomes were generally similar in European and Japanese RA subjects. Mavrilimumab showed rapid (after 1 dose and within 2 wks) and significant clinical effect vs PBO, especially in the 100 mg dose cohort. DAS28 and HAQ-DI responses were maintained for 12 wks after cessation of mavrilimumab 100 mg. The sustained clinical activity and acceptable safety profile supports further clinical development of this new anti-GM-CSFRα mAb. Acknowledgements: This study was sponsored by MedImmune. Disclosure of Interest : G. Burmester Grant/research support from: Abbott, BMS, Pfizer, Roche, UCB, Consultant for: Abbott, BMS, MedImmune, MSD, Pfizer, Roche, UCB, Speakers bureau: Abbott, BMS, MSD, Pfizer, Roche, UCB, T. Takeuchi Grant/research support from: Abbott Japan Co. Ltd, Astellas Pharma Inc., Bristol-Myers Squibb, Chugai Pharmaceutical Co. Ltd, Daiichi Sankyo Co. Ltd, Eisai Co. Ltd, Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Nippon Shinyaku Co. Ltd, Novo Nordisk Pharma Ltd, Otsuka Pharmaceutical Co. Ltd, Pfizer Japan Inc., Sanofi K.K., Santen Pharmaceutical Co. Ltd, Takeda Pharmaceutical Co. Ltd and Teijin Pharma Ltd., O. Barbarash Consultant for: Quintiles, Novartis, Abbott, Takeda, Parexel, Roche, G. Ranganna Employee of: MedImmune, D. Close Employee of: MedImmune, A. Godwood Shareholder of: AstraZeneca, Employee of: MedImmune, D. Saurigny Shareholder of: AstraZeneca, Employee of: MedImmune